Review of intra-ASEAN nontariff measures on trade in goods - Erlinda M. Medalla; Melalyn C. Mantaring (Philippine Institute for Development Studies (PIDS), 2017)
The Association of Southeast Asian Nations (ASEAN) has been working toward the free movement of goods in the region. Although significant progress has been made in the opening up of markets through tariff elimination, addressing the issues on nontariff measures (NTMs) remain. With the reduction in tariffs across the globe, increasing attention has thus shifted to the effects of these NTMs that become simply nontariff barriers (NTBs) to trade. NTMs could be justified for different reasons, such as health, security, environment, and consumer protection. However, they could adversely affect the global and regional production chains by unnecessarily increasing the cost of doing business.This paper reviews existing studies on NTMs for better understanding of NTM implications to international trade, as well as to local business, and to propose some ways forward. For additional insights, it presents the results of the small sample survey (perception) among exporters on the types of NTMs encountered within and outside ASEAN, and the perceived operating cost impact of NTMs. The survey identifies three main NTBs affecting operations of their businesses either within or outside ASEAN: (1) Custom formalities, (2) rules of origin, and (3) technical barriers to trade (TBTs). These are consistent with the findings of an International Trade Center Business Survey on NTMs in the Philippines in 2015-2016. Some of the policy recommendations of the paper are creating a comprehensive and updated database of NTMs, intensive reforms to streamline NTM procedures, improvements in testing laboratories and facilities, accreditation and certification process, and capacity building on what and how to comply with applicable sanitary and phytosanitary measures, and TBTs.
Keywords: 330; ASEAN; non-tariff measures (NTMs); non-tariff barriers (NTBs); sanitary and phytosanitary (SPS) measures; technical barriers to trade (TBTs); trade in goods; rules of origin